Acute beetroot juice supplementation has no effect on upper- and lower-body maximal isokinetic strength and muscular endurance in international-level male gymnasts - Esen, O.; Fox, J.; Karayigit, R.; Walshe, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Nitrate (NO3-) has properties that can improve muscle function, leading to improvements in metabolic cost of exercise as well as enhance force production. Gymnastics is a whole-body sport, involving events that demand a high level of strength and fatigue resistance. However, the effect of NO-3 supplementation on both upper- and lower-body function in gymnasts is unknown. This study examined the effect of acute beetroot juice (BRJ) supplementation on isokinetic strength and endurance of the upper- and lower-body in highly trained international-level male gymnasts. In a double-blind, randomized crossover design, 10 international-level male gymnasts completed two acute supplementation periods, consuming either 2 × 70 ml NO-3-rich (~12.8 mmol/L of NO3-) or NO3--depleted (PLA) BRJ. Maximal strength of the upper-leg and upper-arm at 60°/s, 120°/s, 180°/s, and 300°/s, and muscular endurance (50 repeated isokinetic contractions at 180°/s) were assessed. Plasma NO3- (BRJ: 663 ± 164 µM, PLA: 89 ± 48 µM) and nitrite (NO2-) concentrations (BRJ: 410 ± 137 nmol/L, PLA: 125 ± 36 nmol/L) were elevated following BRJ compared to PLA (both p < .001). Maximal strength of knee and elbow extensors and flexors did not differ between supplements (p > .05 for all velocities). Similarly, fatigue index of knee and elbow extension and flexion was not different between supplements (all p > .05). Acute BRJ supplementation, containing ~12.8 mmol/L of NO3-, increased plasma NO3- and NO2- concentrations, but did not enhance isokinetic strength or fatigue resistance of either upper or lower extremities in international-level male gymnasts.